Nature of bonding in Si2M clusters doped with monovalent metals (M = Li, Na, K, Cu, and Cr) - Thúy Kiều, Nguyễn Thị; Duyên, Phạm Thị Thùy; Hiền, Võ Thị Thanh; Nhung, Phạm Thị Hồng; Ngân, Vũ Thị; Dương, Trần; Thạch, Phạm Ngọc (Hue University Journal of Science: Natural Science, 2020)
The density functional theory at the B3P86/6-311+G(d) level was used to study the geometric structures, stability, and chemical bonding of doped silicon clusters Si2M (M = Li, Na, K, Cu, and Cr). The results reveal that the most stable isomers of Si2M have isosceles triangle structure with the C2v symmetry, existing in two quasi-degenerate electronic states of A1 and B1 at the same spin multiplicity (doublet or quintet). The Si–M bonds are mainly formed via the electron transfer from the AO-s of M atoms to the Si2 moiety in the case of M being Li, Na, and K, while via the overlap between AO-s and AO-3d of Cu, Cr atoms and the MO-s of the Si2 moiety. The Si2Cr cluster is the most stable in the considered clusters.